2022
DOI: 10.3390/pathogens12010031
|View full text |Cite
|
Sign up to set email alerts
|

Low Transmission of Chikungunya Virus by Aedes aegypti from Vientiane Capital, Lao PDR

Abstract: In 2012–2013, chikungunya virus (CHIKV) was the cause of a major outbreak in the southern part of Lao People’s Democratic Republic (Lao PDR). Since then, only a few imported cases, with isolates belonging to different lineages, were recorded between 2014 and 2020 in Vientiane capital and few autochthonous cases of ECSA-IOL lineage were detected in the south of the country in 2020. The CHIKV epidemiological profile contrasts with the continuous and intensive circulation of dengue virus in the country, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In Brazil, the main vectors associated with the transmission of these CHIKV lineages are the mosquitoes Aedes aegypti and Aedes albopictus , both of which are widely distributed across the country [ 7 ]. Previous studies have shown that these two Aedes species are competent vectors for both the ECSA and Asian lineages across different regions of the world [ 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, in Brazil, the impact of locally circulating CHIKV genotypes and specific combinations of local Aedes aegypti populations on the vector competence has not been thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the main vectors associated with the transmission of these CHIKV lineages are the mosquitoes Aedes aegypti and Aedes albopictus , both of which are widely distributed across the country [ 7 ]. Previous studies have shown that these two Aedes species are competent vectors for both the ECSA and Asian lineages across different regions of the world [ 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, in Brazil, the impact of locally circulating CHIKV genotypes and specific combinations of local Aedes aegypti populations on the vector competence has not been thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the main vectors associated with the transmission of these CHIKV lineages are the mosquitoes Aedes aegypti and Aedes albopictus, both of which are widely distributed across the country [14,18,20,29]. Previous studies have shown that these two Aedes species are competent vectors for both the ECSA and Asian lineages across different world regions [15,[29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…However, they had no effect on egg numbers but did significantly reduce the survival time and hatching rate. Claver et al [ 8 ] reported relatively modest vector competence for Aedes aegypti in Vientiane, Lao PDR, to transmit the Asian and ECSA-IOL lineages of chikungunya virus, which may be influenced by the longevity and density of female mosquitoes. Leandro et al [ 9 ] evaluated the spatial and temporal association between vector infestation and the occurrence of dengue cases and reported a dynamic pattern indicating significant risks in certain areas of Foz do Iguaçu, Brazil, based on the entomological–virological index, while entomological indices were not effective in measuring dengue risk.…”
mentioning
confidence: 99%